Estimating the Factors Influencing Liquidity Risk: Empirical Analysis of Indian Non-Banking Financial Institutions - KUMAR, Gaurav; A.V.N., Murty; JEELAKARRA, Srinivas Ravi Kumar; GANAPATHY, S.; G. R., Savitha; PADHY, Sangram (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).20, 2025)
Liquidity risk refers to NBFC’s ability to fund assets and meet obligations as they come due to reasonable costs. Technological advancements and financial innovations have significantly impacted liquidity management in NBFCs. The decreasing reliance on core deposits, increased dependence on capital markets, and recent financial market disruptions have introduced new challenges for NBFCs in managing liquidity. This study explores various theories, indicators, and factors influencing NBFC liquidity, as well as its implications for an NBFC's capital and profitability. Using Arellano-Bond estimates, the research empirically analyzes the determinants of liquidity and examines the interrelationship between liquidity, regulatory capital, and profitability through 2-SLS system equations. The findings highlight that NBFCs' size, profitability, leverage, net interest margin, gross non-performing loans, and the Central Bank Policy Rate are significant determinants of NBFC's liquidity. Furthermore, the interaction between liquidity, profitability, and regulatory capital reveals that while NBFCs can enhance liquidity at the expense of profitability, greater liquidity also results in reduced risk. Non-traditional financial service providers use diverse business models, which leads to a variety of potential liquidity risks.